A new approach for converse binary tree traversals - Rani, K. Pushpa; Roja, G..; Sabitha, Ch.; Lakshmi, B. Dhana; Sreeja, S. (International Journal of Engineering and Technology, 2018)
Traversing through the binary tree is the method the way toward going to every node in a predetermined order. There are two ways to deal B with traverse a tree: traversal and converse traversal. Most approaches demonstrate this method using recursive procedures only. Our review paper concentrates on non recursive converse tree traversal .Converse Tree traversal reduces the time complexity if the left sub tree is not present in the binary tree. Converse Tree traversal is similar to tree traversal but in the Converse Right sub tree then left sub tree. The new approach was found to compare tree traversal with converse tree traversal algorithms.